A natural variant of an MYC2 gene in soybean contributes to resistance against the common cutworm - Xiao Li; Dezhou Hu; Zhongyi Yang; Linyan Cai; Mengshan Zhang; Hailun Liu; Dongquan Guo; Shupeng Dong; Changyun Yang; Fang Huang; Deyue Yu; Hui Wang (Proceedings of the National Academy of Sciences, 2025)
Herbivory is destructive for crop production in many regions worldwide. The induced plant response to herbivores promotes resistance; therefore, characterizing the mechanisms underlying natural host resistance is highly important. However, the genetic components of resistance to herbivores in the staple food crop soybean remain elusive. Here, a key defense gene, GmMYC3 , was identified via joint linkage and association mapping in soybean. GmMYC3 encodes an MYC2 transcription factor that is rapidly activated after jasmonic acid treatment or herbivore attack and confers resistance to a major pest, the common cutworm (CCW), in soybean. GmMYC3 positively regulates multiple biotic stress-related genes, among which GmMYC3 triggers high expression of Kunitz-type trypsin inhibitors alongside its homolog GmMYC1 and downstream GmWRKY56 . GmMYC3 overexpression results in massive accumulation of trypsin inhibitors in soybean leaves, interferes with the protein digestion and absorption function in larvae that are fed these leaves, and retards larval and pupal development of the CCW. The results of the field tests of the transgenic plants corroborate the defense role of GmMYC3 . Evolutionary and population genetic analyses suggest that the elite haplotype of GmMYC3 contributes to resistance against the CCW without significant reduction in seed yield and quality. Notably, this haplotype appears at a low frequency in domesticated germplasms. This study sheds light on the molecular mechanism underlying plant resistance to the CCW and provides potentially valuable resources for breeding soybean plants with elevated resistance against this pest.